PENGARUH LATIHAN LADDER ( BILLY SIMS CROSSOVER : IN AND TWO STEP OUT ) TERHADAP KELINCAHAN TIM SEPAKBOLA SMK TARUNA PEKANBARU KECAMATAN TAMPAN - Gilang Ramadhan; Slamet '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Problems encountered in the study at Football Team Vocational High School Taruna Pekanbaru Tampan District was still weak the agility of the players on the Football team Vocational High School Taruna Pekanbaru District of Tampan, it was seen from several trials and official games done, so the lack of agility that was the causes of the defeat. The type of research was a kind of experimental research to see the effects of the form of exercise. The objective of the research was to look at the effects of Ladder exercise (Billy Sims crossover: in and two step-out) on the agility of football team Vocational High School Taruna Pekanbaru District of Tampan. The population in this research was a soccer team of Vocational High School Taruna Pekanbaru District of Tampan totaling 16 people. Sampling was taken by using total sampling, where the total population was used as sample. Data collection techniques derived from the pre-test and post test. Instrument in this research used the Illinois agility run test as a tool for measuring the agility. Analyses were performed by using t-test. Based on data analysis and discussion, it could be concluded that there was significant influence of Ladder exercise (Billy Sims crossover: in and two step-out) on the football team agility Vocational High School Taruna Pekanbaru District of Tampan proven by Tcount by 14 and Ttable 1.753. It Meant that Tcount > Ttable. At the level of α = 0.05.Keywords: Ladder (Billy Sims Crossover: Two Step In And Out), Agility, Football.